2011
DOI: 10.1186/1476-4598-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Impacting tumor cell-fate by targeting the inhibitor of apoptosis protein survivin

Abstract: Survivin (BIRC5), a member of the inhibitor of apoptosis protein (IAP) family that inhibits caspases and blocks cell death is highly expressed in cancer and is associated with a poorer clinical outcome. Functioning simultaneously during cell division and apoptosis inhibition, survivin plays a pivotal role in determining cell survival. Survivin has consistently been identified by molecular profiling analysis to be associated with higher tumor grade, more advanced disease, abbreviated survival, accelerated rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 123 publications
(125 reference statements)
1
110
1
7
Order By: Relevance
“…Furthermore, survivin is required for stabilization of spindle microtubules and accurate chromosome segregation during mitosis. However, the exact roles of survivin in regulation of cell division and apoptosis are still unclear (Zaffaroni and Daidone, 2002;Zaffaroni et al, 2005;Kelly et al, 2011;Church and Talbot, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survivin is required for stabilization of spindle microtubules and accurate chromosome segregation during mitosis. However, the exact roles of survivin in regulation of cell division and apoptosis are still unclear (Zaffaroni and Daidone, 2002;Zaffaroni et al, 2005;Kelly et al, 2011;Church and Talbot, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of HSPD1 may be potentially associated with the progression and prognosis of prostate cancer (Cornford et al, 2000). HSPD1 could suppress tumor cell apoptosis by maintaining stability of mitochondria (Ghosh et al, 2010), restraining p53 and enhancing a common cancer gene called survivin (Ghosh et al, 2008;Kelly et al, 2011). HSPD1 has also been demonstrated to be associated with early onset of hormone refractory disease in advanced prostate cancer patients under androgen ablation therapy (Castilla et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In general, ovarian carcinomas accompanied by endometriosis show relatively higher level of 8-hydroxy-2′-deoxyguanosine (8-OHdG), which indicates severe oxidative DNA damage, 15 in line with our results demonstrating that pp65 scores were significantly higher in OCCCs as compared with the other subtypes of ovarian carcinomas. Given that the extrinsic apoptotic pathway is activated by cell death receptors, such as TNF-α receptors, 30,31 it is suggested that both extrinsic and intrinsic apoptotic pathways may be activated in OCCCs. With regard to overexpression of exogenous HNF-1β by treatment of the stable cells with doxorubicin, it appeared that toxic insults may also contribute to the regulation.…”
Section: Discussionmentioning
confidence: 99%